Bio-based self-repairing slurry as well as preparation method and application thereof
By introducing microcapsules with dual repair mechanisms into bio-based coatings, the problem of insufficient mechanical properties and durability of traditional bio-based coatings is solved, and the self-repair and durability of the coating is achieved.
Patent Information
- Application Number
- CN202411409763.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional bio-based coatings are particularly difficult to achieve self-repair due to weak mechanical properties and insufficient durability, resulting in a shorter coating service life.
Using a preparation method of bio-based self-healing slurry, the lignin depolymerization product is treated through high-temperature alkaline environment, and copolymerized with isocyanate to form lignin-based polyurethane prepolymer, and the chain extender and emulsifier are added to form microcapsules to achieve Dual repair mechanism.
Through the dual repair mechanism of dynamic covalent bond self-healing microcapsules, the durability and service life of the coating are improved, and the coating can be repaired in minor damage and release core repair agents for deep repair in severe damage.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyurethane materials, and in particular to a bio-based self-repairing slurry and a preparation method and application thereof. Background Art
[0002] Bio-based coating materials have received extensive attention in recent years, such as coating materials based on polylactic acid (PLA), polyhydroxyalkanoates (PHA), chitosan, etc. Such materials have significant advantages in terms of environmental protection and biodegradability. However, traditional bio-based coatings usually have problems such as weak mechanical properties and insufficient durability. In particular, when the coating is damaged, it is difficult to achieve self-repair, resulting in a shortened coating service life.
[0003] The Chinese invention with application number 202211454567.7 discloses a tough light-controlled self-healing lignin-based polyurethane and its preparation method and application. The lignin-based polyurethane is obtained by reacting the following components in parts by mass: 70 to 95 parts of long-chain diols, 5 to 30 parts of low-molecular-weight lignin, 100 parts of lignin and long-chain diols in total, isocyanate (R = 1.1 to 1.5), 1 to 5 parts of reactive ligands, 1 to 5 parts of coordination agents, and 0.2 to 0.5 parts of catalysts. The phenolic hydroxyl groups of low-molecular-weight lignin are used to construct dynamic phenolic hydroxyl-type urethane bonds, and interfacial metal coordination bonds are constructed between the polyurethane chain segments and lignin to form a dynamic double-crosslinked network structure, which greatly improves the strength and toughness of lignin-based polyurethane. However, the lignin-based polyurethane of the above technical solution relies on a single repair mechanism, which makes it difficult to deal with both minor and severe damage at the same time, resulting in unsatisfactory repair effects. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a bio-based self-healing slurry with a dual repair mechanism and a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a bio-based self-healing slurry, comprising the following steps:
[0006] (1) treating lignin in a high temperature alkaline environment to obtain a lignin depolymerization product, and hydroxylating the lignin depolymerization product to obtain hydroxylated depolymerized lignin;
[0007] (2) copolymerizing hydroxylated depolymerized lignin with isocyanate to obtain a lignin-based polyurethane prepolymer, adding a solvent and an amine aqueous solution to the lignin-based polyurethane prepolymer for sufficient reaction, and then removing the solvent to obtain a lignin-based polyurethane;
[0008] (3) adding a chain extender, a solvent and an emulsifier to the lignin-based polyurethane obtained in step (2) to form an O / W type emulsion, heating and curing the emulsion to form a capsule wall of the microcapsule, separating the cured microcapsule particles by centrifugation, washing and drying, and obtaining a dual repair mechanism microcapsule;
[0009] (4) Adding the dual repair mechanism microcapsules obtained in step (3) into the lignin-based polyurethane, stirring and dispersing the mixture to obtain a bio-based self-repairing slurry.
[0010] Furthermore, the method for preparing the above-mentioned bio-based self-healing slurry includes at least one of the following technical features:
[0011] In the step (1), the lignin is selected from at least one of lignins prepared from rice husk, fungus grass, and wheat straw;
[0012] In the step (2), the isocyanate comprises isophorone diisocyanate; the solvent comprises acetone, and the amine aqueous solution comprises ethylenediamine and triethylamine;
[0013] In the step (3), the chain extender includes 4,4'-diaminodiphenyl disulfide; the solvent includes N,N-dimethylformamide; and the emulsifier is a combination of Tween 80 and PVP.
[0014] Furthermore, in the method for preparing the above-mentioned bio-based self-healing slurry, in the step (4), the dual-healing mechanism microcapsules obtained in the step (3) are added to the lignin-based polyurethane in an amount of 5-10wt%.
[0015] Furthermore, in the above-mentioned method for preparing the bio-based self-repairing slurry, the method for preparing the lignin depolymerization product in step (1) is:
[0016] The lignin, NaOH and water were stirred evenly, and Ni / BC catalyst was added, and hydrothermal reaction was carried out at 200-220° C. for 2-3 hours. After cooling, the lignin depolymerization product was obtained by filtering.
[0017] Furthermore, in the above-mentioned method for preparing the bio-based self-repairing slurry, the preparation method of the hydroxylated depolymerized lignin in step (1) is:
[0018] The pH value of the lignin depolymerization product is adjusted to 9.7-10.7, formaldehyde is added, and the reaction is carried out at 80-90° C. for 1-1.5 hours, and then the hydroxylated depolymerized lignin is obtained after cooling.
[0019] Furthermore, in the preparation method of the above-mentioned bio-based self-healing slurry, the step (2) is specifically as follows: adding hydroxylated polylignin, tartaric acid and isophorone diisocyanate into a three-necked flask and performing mechanical stirring, reacting in a nitrogen atmosphere at 100-110°C for 4-5 hours to obtain a lignin-based polyurethane prepolymer, cooling the obtained lignin-based polyurethane prepolymer to 30-40°C, then adding acetone, and then dripping an amine aqueous solution including ethylenediamine and triethylamine into the three-necked flask, continuously stirring for 20-30 minutes, and removing the acetone to obtain a lignin-based polyurethane.
[0020] Furthermore, in the above-mentioned method for preparing the bio-based self-healing slurry, the step (3) is specifically as follows:
[0021] Dissolve 4,4'-diaminodiphenyl disulfide in an organic solvent N,N-dimethylformamide and stir until completely dissolved to form a uniform solution; add the lignin-based polyurethane obtained in step (2) to the uniform solution and stir to obtain a mixed solution; slowly drop the mixed solution into a deionized water phase containing Tween 80 and PVP at a stirring speed of 1000-2000 rpm to form an O / W type emulsion; slowly heat the emulsion to 50-60°C and maintain for 2-3 hours to promote the polymerization reaction of 4,4'-diaminodiphenyl disulfide and solidify to form the capsule wall of the microcapsule; during the heating process, stir to prevent the particles from settling; separate the solidified microcapsule particles by centrifugation; repeatedly wash with deionized water to remove the unreacted substances and residual solvent on the surface; dry the washed microcapsules in a vacuum drying oven at 40-50°C for 6-8 hours to obtain dry dual repair mechanism microcapsules.
[0022] Furthermore, in the preparation method of the above-mentioned bio-based self-healing slurry, the bio-based self-healing slurry is prepared using raw materials in the following weight ratio, including 10-30 parts of lignin, 5-12.5 parts of NaOH, 20-35 parts of water, 0.5-2.0 parts of Ni / BC catalyst, 3-6.5 parts of formaldehyde, 5-8 parts of tartaric acid, 15-25 parts of isocyanate, 2-5 parts of amine aqueous solution, 1-2 parts of Tween80 and 0.5-1 part of PVP.
[0023] Another technical solution provided by the present invention is to provide a bio-based self-healing slurry prepared by the above preparation method.
[0024] Another technical solution provided by the present invention is to provide an application of the above-mentioned bio-based self-repairing slurry in the field of coatings.
[0025] The beneficial effects of the present invention are as follows: the present application proposes a bio-based coating with a dual repair mechanism. By introducing dynamic covalent bond self-healing microcapsules, the microcapsules adopt a dual repair mechanism. The polymerization reaction of 4,4'-diaminodiphenyl disulfide is solidified to form the capsule wall of the microcapsule; the lignin-based polyurethane resin is the core material. When the coating is slightly damaged, the dynamic covalent bonds of the capsule wall material react to repair the coating. When the coating is severely damaged, the capsule wall ruptures and releases the core repair agent to achieve deep repair, thereby greatly improving the durability and service life of the coating. DETAILED DESCRIPTION
[0026] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation methods.
[0027] The key technical concept of this application is:
[0028] 1. The hydroxylated depolymerized lignin structure contains aromatic rings, which has greatly improved mechanical properties, wear resistance and other aspects compared to traditional bio-based materials. It can increase the skeleton stiffness of polyurethane, has good adhesion, and the mechanical properties, stiffness and hardness of the coating are also improved.
[0029] 2. Pure bio-based coatings cannot automatically repair themselves after being damaged. By introducing dynamic covalent self-healing microcapsules, the microcapsules adopt a dual repair mechanism. The polymerization reaction of 4,4'-diaminodiphenyl disulfide solidifies to form the capsule wall of the microcapsule; lignin-based polyurethane resin is used as a repair agent. When the coating is slightly damaged, the dynamic covalent bonds of the capsule wall material react to repair the coating. When the coating is severely damaged, the capsule wall ruptures and releases the core repair agent to achieve deep repair, thereby greatly improving the durability and service life of the coating.
[0030] Example 1
[0031] A method for preparing a bio-based self-healing slurry, wherein the bio-based self-healing slurry is prepared using raw materials in the following weight ratio, including 10-30 parts of lignin, 5-12.5 parts of NaOH, 20-35 parts of water, 0.5-2.0 parts of Ni / BC catalyst, 3-6.5 parts of formaldehyde, 5-8 parts of tartaric acid, 15-25 parts of isophorone diisocyanate, 2-5 parts of amine aqueous solution, 1-2 parts of Tween80 and 0.5-1 part of PVP.
[0032] The preparation method comprises the following steps:
[0033] Stir lignin, NaOH and water evenly, add Ni / BC catalyst, hydrothermally react at 220°C for 3h, cool to room temperature, and filter to obtain lignin depolymerization product. Adjust the pH value of the lignin depolymerization product to 10.7, add 3.7g formaldehyde, react at 90°C for 1.5h, and cool to room temperature to obtain hydroxylated depolymerized lignin;
[0034] Hydroxylated polylignin, tartaric acid and isophorone diisocyanate (IPDI) were added to a three-necked flask and mechanically stirred. The reaction was carried out at 110°C in a nitrogen atmosphere for 5 hours. The obtained lignin-based polyurethane prepolymer was cooled to 40°C and then acetone was added. Then an aqueous amine solution, including ethylenediamine (EDA) and triethylamine (TEA), was dripped into the flask and stirred for 30 minutes. After removing the acetone, a lignin-based polyurethane resin was obtained.
[0035] Dissolve 4,4'-diaminodiphenyl disulfide in an appropriate amount of organic solvent N,N-dimethylformamide (DMF) and stir until completely dissolved to form a uniform solution. Add all the lignin-based polyurethanes obtained above to the uniform solution and continue stirring to make them uniformly dispersed in the solution. The mixed solution is slowly added to the deionized water phase containing 1wt% Tween 80 and 0.5wt% polyvinylpyrrolidone (PVP) at a stirring speed of 2000rpm to form an O / W type emulsion. The emulsion is slowly heated to 60°C and maintained for 2-3 hours to promote the polymerization reaction of 4,4'-diaminodiphenyl disulfide and solidify to form the capsule wall of the microcapsule. During the heating process, moderate stirring is maintained to prevent particle sedimentation. The solidified microcapsule particles are separated by centrifugation, and are repeatedly washed with deionized water to remove the unreacted substances and residual solvents on the surface. The washed microcapsules are dried in a vacuum drying oven at 50°C for 8 hours to obtain dry dual repair mechanism microcapsules.
[0036] The obtained dual-repair mechanism microcapsules are added into lignin-based polyurethane (the lignin-based polyurethane here is prepared in advance and can be prepared by the above-mentioned lignin-based polyurethane preparation method) in an amount of 8wt%, and after stirring and dispersing, a bio-based self-repairing slurry (dual self-repairing lignin-based waterborne polyurethane coating) is obtained.
[0037] Example 2
[0038] A method for preparing a bio-based self-repairing slurry comprises the following steps:
[0039] 12.2g of wheat straw lignin, 4.1g of NaOH and 15g of water were stirred evenly, 0.5g of Ni / BC catalyst was added, and the mixture was hydrothermally reacted at 220°C for 3h. After cooling to room temperature, the lignin depolymerization product was filtered to obtain the lignin depolymerization product. The pH value of the lignin depolymerization product was adjusted to 10.7, 3.7g of formaldehyde was added, and the mixture was reacted at 90°C for 1.5h. After cooling to room temperature, the hydroxylated depolymerized lignin was obtained.
[0040] 35g of hydroxylated depolymerized lignin, 5.8g of tartaric acid and 16ml of isophorone diisocyanate (IPDI) were added to a three-necked flask and mechanically stirred. The reaction was carried out at 110°C in a nitrogen atmosphere for 5 hours. The obtained lignin-based polyurethane prepolymer was cooled to 40°C, and then 35ml of acetone was added. Then 10ml of an amine aqueous solution, including 0.018mol of ethylenediamine (EDA) and 0.024mol of triethylamine (TEA), was dripped into the flask and stirred for 30min. After removing the acetone, a lignin-based polyurethane resin was obtained.
[0041] 20g of 4,4'-diaminodiphenyl disulfide was dissolved in an appropriate amount of organic solvent N,N-dimethylformamide (DMF) and stirred until completely dissolved to form a uniform solution. All the lignin-based polyurethane obtained above was added to the solution and stirred continuously to make it uniformly dispersed in the solution. The mixed solution was slowly added dropwise to the deionized water phase containing 1wt% Tween 80 and 0.5wt% PVP at a stirring speed of 2000rpm to form an O / W type emulsion. The emulsion was slowly heated to 60°C and maintained for 2-3 hours to promote the polymerization reaction of 4,4'-diaminodiphenyl disulfide and solidify to form the capsule wall of the microcapsule. During the heating process, moderate stirring was maintained to prevent particle sedimentation. The solidified microcapsule particles were separated by centrifugation, and the unreacted substances and residual solvents on the surface were removed repeatedly with deionized water. The washed microcapsules were dried in a vacuum drying oven at 50°C for 8 hours to obtain dry dual repair mechanism microcapsules.
[0042] The obtained dual-repair mechanism microcapsules are added into lignin-based polyurethane (the lignin-based polyurethane here is prepared in advance) at an amount of 5 wt %, and the bio-based self-repairing slurry (dual self-repairing lignin-based waterborne polyurethane coating) is obtained after stirring and dispersing.
[0043] Example 3
[0044] A method for preparing a bio-based self-repairing slurry comprises the following steps:
[0045] 26g rice husk lignin, 7.8g NaOH and 20.6g water were stirred evenly, 0.7g Ni / BC catalyst was added, and the mixture was hydrothermally reacted at 220°C for 3h. After cooling to room temperature, the lignin depolymerization product was filtered to obtain the lignin depolymerization product. The pH value of the lignin depolymerization product was adjusted to 10.5, 5.1g formaldehyde was added, and the mixture was reacted at 90°C for 1.5h. After cooling to room temperature, the hydroxylated depolymerized lignin was obtained.
[0046] 44.5 g of hydroxylated depolymerized lignin, 8.8 g of tartaric acid and 20 ml of isophorone diisocyanate (IPDI) were added to a three-necked flask and mechanically stirred. The reaction was carried out at 110 ° C in a nitrogen atmosphere for 5 hours. All the lignin-based polyurethane prepolymers obtained above were cooled to 40 ° C, and then 45 ml of acetone was added. Then 15 ml of an amine aqueous solution, including 0.024 mol of ethylenediamine (EDA) and 0.040 mol of triethylamine (TEA), was dripped into the flask and stirred for 30 minutes. After removing the acetone, a lignin-based polyurethane resin was obtained.
[0047] 30g of 4,4'-diaminodiphenyl disulfide was dissolved in an appropriate amount of organic solvent N,N-dimethylformamide (DMF) and stirred until completely dissolved to form a uniform solution. The above-mentioned lignin-based polyurethane was added to the solution and stirred continuously to make it uniformly dispersed in the solution. The mixed solution was slowly added dropwise to the deionized water phase containing 2wt% Tween 80 and 0.5wt% PVP at a stirring speed of 2000rpm to form an O / W type emulsion. The emulsion was slowly heated to 60°C and maintained for 2-3 hours to promote the polymerization reaction of 4,4'-diaminodiphenyl disulfide and solidify to form the capsule wall of the microcapsule. During the heating process, moderate stirring was maintained to prevent particle sedimentation. The solidified microcapsule particles were separated by centrifugation, and the unreacted substances and residual solvents on the surface were removed repeatedly with deionized water. The washed microcapsules were dried in a vacuum drying oven at 50°C for 8 hours to obtain dry dual repair mechanism microcapsules.
[0048] The obtained dual-repair mechanism microcapsules are added into lignin-based polyurethane in an amount of 10 wt %, and the bio-based self-repairing slurry (dual self-repairing lignin-based waterborne polyurethane coating) is obtained after stirring, dispersing and mixing.
[0049] Comparative Example 1
[0050] The difference between Comparative Example 1 and Example 1 is that the hydroxylated depolymerized lignin is replaced with castor oil;
[0051] 35g of castor oil, 5.8g of tartaric acid and 16ml of isophorone diisocyanate (IPDI) were added to a three-necked flask and mechanically stirred. The reaction was carried out at 110°C under a nitrogen atmosphere for 5 hours. The obtained castor oil-based polyurethane prepolymer was cooled to 40°C, and then 35ml of acetone was added. Then 10ml of an amine aqueous solution, including 0.018mol EDA and 0.024mol TEA, was dripped into the flask, stirred for 30min, and castor oil-based polyurethane resin was obtained after removing acetone.
[0052] 20g of 4,4'-diaminodiphenyl disulfide was dissolved in an appropriate amount of organic solvent N,N-dimethylformamide (DMF) and stirred until completely dissolved to form a uniform solution. The castor oil-based polyurethane was added to the solution and stirred continuously to make it uniformly dispersed in the solution. The mixed solution was slowly added dropwise to a deionized water phase containing 1wt% Tween 80 and 1wt% PVP at a stirring speed of 2000rpm to form an O / W type emulsion. The emulsion was slowly heated to 60°C and maintained for 2-3 hours to promote the polymerization reaction of 4,4'-diaminodiphenyl disulfide and solidify to form the capsule wall of the microcapsule. During the heating process, moderate stirring was maintained to prevent particle sedimentation. The solidified microcapsule particles were separated by centrifugation, and the unreacted substances and residual solvents on the surface were removed repeatedly with deionized water. The washed microcapsules were dried in a vacuum drying oven at 50°C for 8 hours to obtain dry dual repair mechanism microcapsules.
[0053] The obtained dual repair mechanism microcapsules are added into castor oil-based polyurethane in an amount of 8 wt %, and the dual self-repairing castor oil-based waterborne polyurethane coating is obtained after stirring, dispersing and mixing.
[0054] Comparative Example 2
[0055] Comparative Example 2 is different from Example 1 in that no self-repairing capsule is added.
[0056] 12.2g of wheat straw lignin, 4.1g of NaOH and 15g of water were stirred evenly, 0.5g of Ni / BC catalyst was added, and the mixture was hydrothermally reacted at 220°C for 3h. After cooling to room temperature, the lignin depolymerization product was filtered to obtain the lignin depolymerization product. The pH value of the lignin depolymerization product was adjusted to 10.7, 3.7g of formaldehyde was added, and the mixture was reacted at 90°C for 1.5h. After cooling to room temperature, the hydroxylated depolymerized lignin was obtained.
[0057] 35g of hydroxylated depolymerized lignin, 5.8g of tartaric acid and 16ml of isophorone diisocyanate (IPDI) were added to a three-necked flask and mechanically stirred. The reaction was carried out at 110°C under a nitrogen atmosphere for 5 hours. The obtained lignin-based polyurethane prepolymer was cooled to 40°C and then 35ml of acetone was added. Then 10ml of an amine aqueous solution, including 0.018mol EDA and 0.024mol TEA, was dripped into the flask and stirred for 30min. After removing the acetone, the lignin-based polyurethane was obtained.
[0058] Comparative Analysis of the Examples and Comparative Examples
[0059] The coating carrier material of the bio-based self-repairing slurry obtained in this application can be applied to fabrics or shoe uppers, and can self-repair at room temperature. The generally preset thickness is 0.5-2.4 mm, and the thickness used below is 1 mm;
[0060] 1. Test the wear resistance of the printed products of each embodiment
[0061] The printed product obtained in the application example was tested for wear resistance using a Taber wear tester. Referring to the standard QB T 4545-2013, the printed product was placed on a rotating platform, and the two friction wheels above it were driven to roll by the rotating platform. The friction wheels rotated and rubbed the printed product under the same load to wear the sample. One friction wheel faced outward, and the other friction wheel faced inward to rub the sample. The wear mark was an overlapping ring. After rubbing at a specified frequency, the number of circles when the cloth was worn out was recorded. The test results are shown in Table 1.
[0062] Table 1 Wear resistance test results of products
[0063] Serial number Example 2 Example 3 Comparative Example 1 Comparative Example 2 Number of rupture circles 3500 3200 1500 2800
[0064] From the wear test results in Table 1, it can be seen that the lignin-based polyurethane coating of the present application can greatly improve the wear resistance of the bio-based coating printed products compared with the castor oil-based polyurethane coating, and the wear resistance of the coating with the addition of double self-healing capsules is also improved.
[0065] 2. Testing the bending resistance of the printed products of each embodiment
[0066] The bending resistance tester was used to test the bending resistance of the printed finished product obtained in the above application embodiment. Referring to the standard QBT 3903.41-2008, a sample with a size of (70±1mm)×(45±1mm) was taken at the same position of the sample. First, the front or grain surface of the sample was folded inward and one end of the sample was clamped in the upper clamp to ensure that the sample surface was in contact and the folding line was horizontal. Then the inside of the sample was folded outward 90° and clamped in the lower clamp. In the lower clamp, the sample was also folded, the folding line was vertical, and the reverse side or flesh side of the sample was in contact. This test simulates the damage to the upper surface caused by the inward bending of the upper surface due to movement. During the test, the clamp swung at a constant rate and the sample was bent repeatedly. At room temperature, dry or wet tests can be carried out, or dry tests can be carried out below zero degrees. After reaching the specified number of swings, the test was stopped and the damage or salting out of the test was visually tested. The test results show that the addition of dual self-repairing lignin-based polyurethane slurry can pass the bending resistance test within a certain range. The bending resistance test results are shown in Table 2.
[0067] Table 2 Product bending resistance test results
[0068] Serial number Example 2 Example 3 Comparative Example 1 Comparative Example 2 Bending times 150000 120000 ≤50000 ≤100000
[0069] From the experimental results in Table 2, it can be seen that the bending resistance of lignin-based polyurethane coatings has been significantly improved. Since the depolymerized lignin structure contains aromatic rings, the skeleton stiffness of the polyurethane is increased, and it has good adhesion. The mechanical properties, stiffness and hardness of the coating are also improved.
[0070] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a bio-based self-repairing slurry, characterized in that: The steps include: (1) treating lignin in a high temperature alkaline environment to obtain a lignin depolymerization product, and hydroxylating the lignin depolymerization product to obtain hydroxylated depolymerized lignin; (2) copolymerizing hydroxylated depolymerized lignin with isocyanate to obtain a lignin-based polyurethane prepolymer, adding a solvent and an amine aqueous solution to the lignin-based polyurethane prepolymer for sufficient reaction, and then removing the solvent to obtain a lignin-based polyurethane; (3) adding a chain extender, a solvent and an emulsifier to the lignin-based polyurethane obtained in step (2) to form an O / W type emulsion, heating and curing the emulsion to form a capsule wall of the microcapsule, separating the cured microcapsule particles by centrifugation, washing and drying, and obtaining a dual repair mechanism microcapsule; (4) Adding the dual-repair mechanism microcapsules obtained in step (3) into the lignin-based polyurethane, stirring and dispersing the mixture to obtain a bio-based self-repairing slurry.
2. The method for preparing the bio-based self-repairing slurry according to claim 1, characterized in that: Include at least one of the following technical features: In the step (1), the lignin is selected from at least one of lignins prepared from rice husk, fungus grass, and wheat straw; In the step (2), the isocyanate comprises isophorone diisocyanate; the solvent comprises acetone, and the amine aqueous solution comprises ethylenediamine and triethylamine; In the step (3), the chain extender includes 4,4'-diaminodiphenyl disulfide; the solvent includes N,N-dimethylformamide; and the emulsifier is a combination of Tween 80 and PVP.
3. The method for preparing the bio-based self-repairing slurry according to claim 1, characterized in that: In the step (4), the dual repair mechanism microcapsules obtained in the step (3) are added to the lignin-based polyurethane in an amount of 5-10 wt%.
4. The method for preparing the bio-based self-repairing slurry according to claim 1, characterized in that: The preparation method of the lignin depolymerization product in step (1) is: The lignin, NaOH and water were stirred evenly, and Ni / BC catalyst was added, and hydrothermal reaction was carried out at 200-220° C. for 2-3 hours. After cooling, the lignin depolymerization product was obtained by filtering.
5. The method for preparing the bio-based self-repairing slurry according to claim 4, characterized in that: The preparation method of the hydroxylated depolymerized lignin in step (1) is as follows: The pH value of the lignin depolymerization product is adjusted to 9.7-10.7, formaldehyde is added, and the mixture is reacted at 80-90° C. for 1-1.5 hours, and then cooled to obtain hydroxylated depolymerized lignin.
6. The method for preparing the bio-based self-repairing slurry according to claim 5, characterized in that: The step (2) specifically comprises: adding hydroxylated polylignin, tartaric acid and isophorone diisocyanate into a three-necked flask, and mechanically stirring, reacting under a nitrogen atmosphere at 100-110° C. for 4-5 hours to obtain a lignin-based polyurethane prepolymer, cooling the obtained lignin-based polyurethane prepolymer to 30-40° C., then adding acetone, and then dripping an amine aqueous solution including ethylenediamine and triethylamine into the three-necked flask, continuously stirring for 20-30 minutes, and removing the acetone to obtain a lignin-based polyurethane.
7. The method for preparing the bio-based self-repairing slurry according to claim 6, characterized in that: The step (3) is specifically: Dissolve 4,4'-diaminodiphenyl disulfide in an organic solvent N,N-dimethylformamide and stir until completely dissolved to form a uniform solution; add the lignin-based polyurethane obtained in step (2) to the uniform solution and stir to obtain a mixed solution; slowly drop the mixed solution into a deionized water phase containing Tween 80 and PVP at a stirring speed of 1000-2000 rpm to form an O / W type emulsion; slowly heat the emulsion to 50-60°C and maintain for 2-3 hours to promote the polymerization reaction of 4,4'-diaminodiphenyl disulfide and solidify to form the capsule wall of the microcapsule; during the heating process, stir to prevent the particles from settling; separate the solidified microcapsule particles by centrifugation; repeatedly wash with deionized water to remove the unreacted substances and residual solvent on the surface; dry the washed microcapsules in a vacuum drying oven at 40-50°C for 6-8 hours to obtain dry dual repair mechanism microcapsules.
8. The method for preparing the bio-based self-repairing slurry according to claim 7, characterized in that: The bio-based self-healing slurry is prepared using raw materials in the following weight ratio, including 10-30 parts of lignin, 5-12.5 parts of NaOH, 20-35 parts of water, 0.5-2.0 parts of Ni / BC catalyst, 3-6.5 parts of formaldehyde, 5-8 parts of tartaric acid, 15-25 parts of isocyanate, 2-5 parts of amine aqueous solution, 1-2 parts of Tween80 and 0.5-1 part of PVP.
9. A bio-based self-healing slurry prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the bio-based self-healing slurry according to claim 8 in the field of coatings.
Citation Information
Cited By
Self-repairing long-acting anticorrosive coating material as well as preparation method and application thereof
CN119505678A
